Rancang Bangun Mesin Air Press Assy Otomatis Berbasis PLC - Tri Hannanto Saputra; Cornelius Hendriarto (Indonesian Society of Applied Science (ISAS), 2020)
Motor vehicle light boxes require a lamp holder installation process. This study aims to automate the process of installing a lamp holder into a motorized vehicle light box through the design of an air press machine. The machine has 5 (five) process stages, namely installing the lamp box on the jig, installing the lamp holder, pressing the lamp holder, installing the lamp on the holder, taking the lamp box from the jig. The product is pressed automatically through a cylinder press mechanism. Based on the test results, it is known that the machine takes an average of 9 (nine) seconds to install the lamp and lamp holder into the light box. The result of this machine is that the time produced is 3 (three) seconds faster than the previous machine, which takes an average of 12 (twelve) seconds. The use of machines has the potential to increase productivity and workforce efficiency. The machine in this research can be developed to increase the efficiency of the assembly process.